Comparison of amplitude‐mode ultrasound versus air displacement plethysmography for assessing body composition changes following participation in a structured weight‐loss programme in women. (11th March 2016) - Schoenfeld, Brad J.; Aragon, Alan A.; Moon, Jordan; Krieger, James W.; Tiryaki‐Sonmez, Gul
Summary: The purpose of this study was to compare body composition changes as measured by A‐mode ultrasound (US) versus a criterion densitometry‐based measure, air displacement plethysmography (ADP), over a 4‐week weight‐loss protocol in healthy, non‐obese young women. Twenty healthy, young female volunteers were provided with customized dietary plans for the length of the study intended to facilitate a 500 calorie‐a‐day deficit. Subjects also performed 3 h a week of supervised aerobic exercise. Per cent fat mass and lean body mass were obtained via ADP and US both pre‐ and postintervention. Pretesting, post‐testing and delta data for %fat resulted in no significant differences in mean values along with a slope of the regression line no different than one and a y ‐intercept no different than zero ( P <0·05). Similar to %fat values, pretesting, post‐testing and delta data for fat‐free mass resulted in no significant differences in mean values along with a slope of the regression line no different than one and a y ‐intercept no different than zero ( P <0·05) with the exception of the delta for slope (0·39, P = 0·04). The current findings indicate that US can provide a similar degree of accuracy for tracking group‐based fat loss in women compared to ADP. Given the low‐cost relative to DXA and ADP, researchers and practitioners therefore can consider US as a viable option for monitoring group‐based changes in body fat over time.